An Overview of the Primary Healthcare System in Nigeria - Dada, Sholadoye (MultiTech Publisher, 2023)
This paper describes the structure and operation of the primary healthcare system in Nigeria, the sequence of its evolution from inception to what is obtainable now and the effectiveness of the system. Prior to that, a detailed description of the WHO targets through its Alma-Ata declaration in 1978 was explained and evaluated in comparison with the Nigerian healthcare system. Emphasis was laid on the concept, principle and element of the primary healthcare system as well as the challenges and the current state of the system. In conclusion, Primary healthcare in Nigeria, particularly in rural areas, has come a long way, but more work is undoubtedly still needed to realize the objective of universal health now and in the future. Priority should be given to improving people's living conditions beyond the current poverty level in order to promote healthier living. Local governments, as well as all other levels of government, must increase their allocations to the health sector among other things.